Analisis Kadar Asam Asetat Dalam Media Limbah Fermentasi Biji Kakao Akibat Penambahan Konsentrasi Acetobacter Aceti Dan Waktu Inkubasi - Wiwik Kusmawati (IKIP Budi Utomo Malang, 2017)
This study aims to determine the effect of Acetobacteraceti concentration and incubation time on levels of acetic acid in the vinegar fermentation of cocoa beans waste media. This study uses a completely randomized design (CRD) arranged as factorial, consisting of two factors and repeated three times. The frst factor is the concentration of Acetobacteraceti which consists of three levels, namely Acetobacteraceti starter concentration of 10% (A1), 13% (A2) and 16% (A3). While the second factor is the time of incubation for 6 days (W1), 8 days (W2) and 10 days (W3). Results of analysis of variance showed that the concentration of Acetobacteraceti and incubation time affect the concentration of acetic acid in the vinegar fermentation of cocoa beans waste media. While Duncan’s test results showed the treatment inoculation 13% starter Acetobacteraceti with 6 days of incubation time signifcantly different from the other treatments with maximum acetic acid content is 4,02%. So that these results meet the standards of vinegar.